(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
In Mekong river basin, productivity of rice is still low and unstable because more than 70 % of paddy fields were classified as rain-fed paddy. In addition, future global climate change and land use change will make negative impact on rice production in this region. In order to analyze the stability of rice production quantitatively, it is important to consider the rice farming management such as strategy of rain-fed rice yield stabilization. This management was defined as control their acreage under rice cultivation depended on rainfall amount. In drought year, farmers abandoned some paddies to cultivate rice and collect rain water from abandoned paddies to planted paddies. In this way, statistic data of rice yield was more stable than that of harvested area. In this study, rice production model was developed combined with distributed type water circulation model. This model consists of three sub models, harvested area estimation model used of FAO-33, yield estimation model used of Monteith equations and FAO-56 and rainfall runoff model used of TOPMODEL. Developed rice production model was applied to Mekong river basin. Mekong river basin was divided in 10km mesh grids, and model simulation was conducted in 10km resolution from 1986 to 1995. Simulation result of rice harvested area, yield and production were verified with the statistic data of northeast Thailand. As a result, rice harvested area, yield and production was good agreement with statistic data, and especially error in rice yield was improved by considering the strategy of rain-fed rice yield stabilization.